New challenges to philosophy of science - Dieks, Dennis; Gonzalez, Wenceslao J.; Uebel, Thomas; Wheeler, Gregory; Andersen, Hanne (The Philosophy of Science in a European Perspective, 2013)
This volume is a serious attempt to open up the subject of European philosophy of science to real thought, and provide the structural basis for the interdisciplinary development of its specialist fields, but also to provoke reflection on the idea of 'European philosophy of science'. This efforts should foster a contemporaneous reflection on what might be meant by philosophy of science in Europe and European philosophy of science, and how in fact awareness of it could assist philosophers interpret and motivate their research through a stronger collective identity. The overarching aim is to set the background for a collaborative project organising, systematising, and ultimately forging an identity for, European philosophy of science by creating research structures and developing research networks across Europe to promote its development.